Are social media companies motivated to be good corporate citizens? Examination of the connection between corporate social responsibility and social media safety. (June 2019) - Grygiel, Jennifer; Brown, Nina
Abstract: This paper explores the connection between corporate social responsibility and social media safety. By examining the legal framework governing social platforms in the United States and case studies of online harms, we explore whether current U.S. laws and company content moderation policies are effective in eliminating content (revenge porn and acts of terrorism) that is universally agreed to be harmful. Finally, the paper makes a number of suggestions for improvements in policy.